2009
DOI: 10.1163/22941932-90000202
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mid-Rotation Fertilization on the Wood Properties of Loblolly Pine (Pinus Taeda)

Abstract: Mid-rotation fertilization is a common practice in the management of loblolly pine (Pinus taeda L.) plantations, typically providing large improvements in growth. However, concerns exist about the quality of wood produced following fertilization. The objective of this study was to develop an understanding of wood property changes following fertilization. Wood samples from a study involving four levels of fertilization applied to a thinned mid-rotation loblolly pine plantation located on the lower coastal plain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
3
10
2
Order By: Relevance
“…The radial and longitudinal (i.e., at different tree heights) variations of SG in this study are consistent with previous studies on loblolly pine from plantations [69,70,77,78]. The within-tree variation in SG was captured in a model that predicted SG values against cambial age (Figure 1), while incorporating disk height in the model gave a better fit and showed that predicted values decreased with height in the tree.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The radial and longitudinal (i.e., at different tree heights) variations of SG in this study are consistent with previous studies on loblolly pine from plantations [69,70,77,78]. The within-tree variation in SG was captured in a model that predicted SG values against cambial age (Figure 1), while incorporating disk height in the model gave a better fit and showed that predicted values decreased with height in the tree.…”
Section: Discussionsupporting
confidence: 90%
“…Including the effects of silviculture may have improved the model fit at the expense of model complexity. Antony et al [78] modeled latewood SG and showed that latewood SG decreased with increasing fertilization intensity. Included in their paper is a plot of mean latewood SG with the x-axis in years instead of cambial age to illustrate the decreasing trend.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations